8051 Microcontrollers Fundamental Concepts, Hardware, Software and Applications in Electronics - Gimenez, Salvador Pinillos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook describes in detail the fundamental information about the 8051 microcontroller and it carefully teaches readers how to use the microcontroller to make both electronics hardware and software. In addition to discussion of the 8051 internals, this text includes numerous, solved examples, end-of-chapter exercises, laboratory and practical projects. Explains internals of 8051 hardware and relates to general principles of computer architecture; Demonstrates how to implement various electronics applications, with hardware and software design for 8051 microcontrollers; Includes numerous, solved examples, end-of-chapter exercises, laboratory and practical projects.
Fundamental Concepts of Computer Systems -- 8051 Core Microcontrollers -- 8051 - Core Microcontroller Instruction Set -- Flowchart and Assembly Programming -- Subroutine and Structuring of the Assembly Programming Language -- Input/output Ports of 8051 - Core Microcontrollers -- Basic 8051 - Core Microcontroller Interruptions -- Timers/Counters of the 8051 Core Microcontroller -- The Serial Communication Interface of the 8051 - Core Microcontroller.
Keywords: Electronic circuits; Electronics; Microprocessors; Computer architecture; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation; Processor Architectures